Measurement and modeling of the peer-to-peer sharing objects popularity - GUO Zhen-bin; QIU Zheng-ding (Tongxin xuebao)
A detailed study on the BitTorrent sharing objects popularity was presented.The objects-sharing popularity and objects-downloading popularity of four BitTorrent trackers was measured and modeled by means of actively probing the tracker server, and the model was tested by χ2 fitting test.The experiment results indicate that the peer-to-peer sharing objects popularity is very unbalanced, that is, there are almost 60% of total share copies for the most 20% popular objects and there are above 60% of total downloads for the most 10% popular objects.Moreover, the experiment results also indicate that the objects-sharing popularity can be well modeled by Zipf distribution and perfectly modeled by Zipf-Mandelbrot distribution, and that the objects-downloading popularity can not be modeled by Zipf distribution and can be perfectly modeled by Zipf-Mandelbrot distribution.